USING AI TO DEVELOP AN OPTIMAL MANUFACTURING PROCESS FOR ELECTRONICS - Gautam Nandkishore Nayak (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article examines the transformative impact of artificial intelligence on electronics manufacturing processes and decision-making strategies. The article explores how AI systems optimize key manufacturing parameters including first pass yield, test coverage, cycle time, and cost of quality while revolutionizing supply chain management and quality control. The article analyzes the integration of historical data with real-time processing capabilities, demonstrating how AI-driven systems enhance batch size optimization, material selection, and production planning. Through comprehensive analysis of implementation cases across multiple manufacturing sectors, the research highlights AI's role in improving operational efficiency, reducing costs, and enhancing product quality while maintaining high order fulfillment rates and customer satisfaction levels. The article indicates that AI integration in manufacturing processes not only optimizes current operations but also provides predictive insights for strategic decision-making and future planning